Applications of Big Data in various Domains - Kumarasamy, M; Suresh Babu, GNK (International Journal of Computer Sciences and Engineering, 2025)
The term Big data is very popular recently in all the domains. Every where and every body talking about big data numerously. The goal of this paper is to describe what is big data and how it can be used in various applications. The rising number of applications serving millions of users and dealing with terabytes of data need to a faster processing paradigms. Recently, there is growing enthusiasm for the notion of big data analysis. Big data analysis becomes a very important aspect for growth productivity, reliability and quality of services. Processing of big data using a powerful machine is not efficient solution. So, companies focused on using Hadoop software for big data analysis. This is because Hadoop designed to support parallel and distributed data processing. Hadoop provides a distributed file processing system that stores and processes a large scale of data. The author tries to give the introduction about Hadoop and Map Reduce architecture. The main goal of this paper is applications of big data in various domains and how to build decision support system using big data. Big data have applications in many fields such as Business, Technology, Health Care, Smart cities etc. These applications will allow people to have better services, better customer experiences, and also to prevent and detect illness much easier than before.